Corticosterone Induces Depressive-Like Behavior in Female Peri-Pubescent Rats, but Not in Pre-Pubescent Rats. (May 2020) - Nickle, Tyler R.; Stanley, Erica M.; Middlemas, David S.
Background: There are no data on the effect of exogenous corticosterone on depressive-like behavior in juvenile rats. Furthermore, it has not been tested whether the effects of corticosterone in female rats is different before or after puberty. Objective: We tested the effect of corticosterone treatment on female pre- and peri-pubescent juvenile rats on depressive-like behavior. Methods: Female juvenile rats were divided into pre-pubescent (post-natal day 7–27) or peri-pubescent (post-natal day 28–48) groups and administered daily corticosterone (40 mg kg −1  day −1 ) for 21 days. Depressive-like behavior was assessed using a modified forced swim test and the sucrose preference test. After behavioral assessment, brains were analyzed to determine if there were changes in cell proliferation and newborn neuron survival in the dentate gyrus of the dorsal hippocampus. Results: Chronic corticosterone treatment did not affect behavior or neurogenesis in female pre-pubescent juvenile rats. However, female peri-pubescent rats injected with corticosterone showed increased depressive-like behavior as well as a decrease in cell proliferation in the subgranular zone. Furthermore, there was an inverse correlation between time spent immobile in the forced swim test and cell proliferation in the granule cell layer in peri-pubescent rats. Conclusions: Corticosterone induces depressive-like behavior in peri-pubescent, but not in pre-pubescent female rats. Finally, our results suggest that depressive-like behavior may be associated with a decrease in hippocampal cell proliferation in female peri-pubescent rats.